Management of Transport Interchanges Hubs with A Modified Indicator Method for Assessing Sustainability* - Iwona KRZYŻEWSKA (Communications of International Proceedings, 2024)
In recent years, efforts have been observed aimed at improving the functioning of passengers in the area of integrated transfer hubs. An analysis of literature sources and legal requirements has pointed to a lack of legal regulations in the field of public transport. The absence of guidelines concerns both modes of transport and infrastructure elements with regard to people with special needs. There are insufficient standards and guidelines for the creation, construction, and modification of integrated transfer hubs considering individuals with special needs. Different cities adopt their own studies and best practices, which are used in the design or modernization phases of transfer hubs. This paper presents a modified method for assessing the sustainable management of a transport interchanges nodes.
Keywords: :public transport; integrated interchange; sustainability; accessibility.